Analisis Modalitas Pernyataan Ekonom Terkait Tarif AS: Pendekatan Sistematik-Fungsional Wacana Kebijakan Luar Negeri - Widyaningroh, Karina Emilia; Hamsah, Chantika Deswita; Sa’adah; Alifah, Noer; Kurniawan, Bima (Jurnal Ilmu Sosial dan Budaya Indonesia, 2025)
This study aims to analyze the differences in modality in the statements of two economists regarding the implementation of high US tariffs in Indonesia. Professor of economics at IPB, Didin S. Damanhuri, concluded that the surge in US import tariffs could exacerbate the weakening of the rupiah, reduce purchasing power, and trigger mass layoffs, so a quick and coordinated response is needed to prevent a multidimensional crisis. Similarly, President of the Confederation of Indonesian Trade Unions (KSPI) Said Iqbal warned that the implementation of new import tariffs of 32% from the United States could trigger a second wave of mass layoffs reaching more than 50,000 workers in the next three months due to rising production costs and declining export demand. This study examines the modalities, including aspects of probability, usuality, inclination, and obligation, in the statements of the two economists. The frequency of modality that often appears is probability modulation 3 times and must modulation 10 times. This study using the literature review method contributes to discourse analysis, particularly in the context of foreign policy impact, by showing how linguistic elements such as modality play a role in framing messages and creating public perceptions of economic stability.